2012
DOI: 10.1590/s0100-204x2012000700003
|View full text |Cite
|
Sign up to set email alerts
|

Leaf-cutting ant attack in initial pine plantations and growth of defoliated plants

Abstract: -The objective of this work was to evaluate the natural attack by Acromyrmex crassispinus in initial Pinus taeda plantations without control measures against ants, as well as the effect of defoliation in seedlings of P. taeda. Evaluations of the attack of leaf-cutting ants on P. taeda plantations were done monthly in the first six months, then 9 and 12 months after planting. The percentages of plants that were naturally attacked by ants were registered. The effect of defoliation was evaluated by artificial def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 15 publications
4
31
0
2
Order By: Relevance
“…Artificial defoliation was performed by Nickele et al . (2012) in an area of newly planted P. taeda (planting in August 2007) in São Mateus do Sul (25°58′S, 50°23′W), state of Paraná, Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial defoliation was performed by Nickele et al . (2012) in an area of newly planted P. taeda (planting in August 2007) in São Mateus do Sul (25°58′S, 50°23′W), state of Paraná, Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Ant attacks on pine plants are more frequent in the first months after planting, particularly during the first 30 days. The percentage of attacked plants diminishes in the following months, while the level of defoliation in attacked plants drops below 50% (Nickele et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, ants preferred foraging in plants derived from natural regeneration and they did not attack the plants of commercial interest, which is exotic. Nickele et al (2012b) found that higher percentages of Acromyrmex attack in P. taeda plants occurs in the first months after planting, with larger impact in the first 30 days, in reform areas where earlier planting suffered pruning and thinning. In this case, A. crassispinus nests have been observed since the beginning of planting and the first months after planting, ants had no options of native plant resources for foraging due to soil preparation for planting (Nickele et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…Segundo Buratto et al (2012), com a utilização de iscas formicidas os danos totais médios ocasionados por formigas cortadeiras em mudas de P. taeda no município de Anita Garibaldi, SC, foi no máximo de 5,38% no 63º dia de avaliação. Importante ressaltar que a forma de controle testada, diferentemente do controle com iscas formicidas, não elimina a colônia, permitindo que elas permaneçam ativas, uma vez que, de acordo com Nickele et al (2012), a espécie Acromyrmex crassispinus causa perdas em indivíduos de P. taeda somente nos primeiros meses de idade do plantio, com maior concentração nos primeiros 30 dias em áreas do planalto norte do estado de Santa Catarina. Não foram previamente contados os formigueiros presentes na área, mas o experimento só foi instalado após a confirmação de que havia formiga cortadeira no entorno.…”
Section: Resultados E Discussõesunclassified